ANALISIS MODAL KERJA PADA JAYA REKLAME DI SANGATTA - ., Intan (EKONOMIA, 2013)
Research purposes to determine the level of working capital at Jaya Advertising business in Sangatta , research was carried out for 3 Months ( April to June 2013) at Jaya Advertising Business in Sangatta , related to working capital analysis . Research activities carried out , namely : literature study , field observations , interviews , documentation , data collection and analysis . Data collected in the study include : an overview of companies , Business Legal and financial condition . Analysis tool that is used is to compare the financial statements of the last two periods . From the analysis of sources of working capital acquired by Rp 472,145,697.75 which is derived from the company's operating profit , depreciation , fixed assets , capital , and borrowing from the Bank . While the use of working capital of Rp 593,764,469.75 consisting of the addition of goods - goods inventory of Rp . 43,764,469.75 buy Rp.300.000.000 building , 00membeli vehicles of Rp . 250,000,000.00 led to shortage of working capital of Rp 121,618,772.00 go used in the purchase of fixed assets. Results of research on Jaya Advertising in Sangatta short-term working capital loans used to finance long-term investments . Seen from the point of purchase / fund management appears that working capital is owned by the company have not been utilized as needed , it is seen that most of the many uses of working capital to finance the purchase of fixed assets that do not fit the needs of working capital .